Teacher Strategies for Increasing Students' Interest in Religious Learning - Efendi, Efendi; Ridha, Arif; Zahara, Afrila; Rudiamon, Septika (Al-kayyis: Journal of Islamic Education, 2023)
Teachers play a key role in developing students' interest in moral education. Precisely, This research aims to find out teachers' strategies for increasing students' interest in learning moral lessons. This research uses a qualitative method with a case study approach (case study design). The data source was taken from one informant through in-depth interviews. The informant is a high school Islamic Education Teacher. All interview results were then analyzed thematically using the qualitative analysis software Nvivo 12. Overall the results of the analysis show that there are two teacher strategies for increasing students' interest in learning moral lessons, namely: i) Carrying out direct moral development, ii) Providing motivation to students. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.